O znaczeniu edukacji i terapii artystycznej - kilka refleksji = About meaning of education and artistic therapy. A few reflections - Kataryńczuk-Mania, Lidia (Zielona Góra ; Skarbona: Stowarzyszenie Polskich Muzyków Kameralistów)
The Author comments on cognitive, artistic, educational and therapeutic qualities of education and therapy by art. She refers to professional literature and valid problems of art-therapy suggested in her earlier publications.
Keywords: edukacja artystyczna; terapia sztuką; arteterapia - rodzaje; artistic education; art therapy; sorts of art-therapy